The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3390/ijms151017396
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and Transcriptional Analysis of the Biosynthesis Gene Cluster of Abscisic Acid-Producing Botrytis cinerea

Abstract: Botrytis cinerea is a model species with great importance as a pathogen of plants and has become used for biotechnological production of ABA. The ABA cluster of B. cinerea is composed of an open reading frame without significant similarities (bcaba3), followed by the genes (bcaba1 and bcaba2) encoding P450 monooxygenases and a gene probably coding for a short-chain dehydrogenase/reductase (bcaba4). In B. cinerea ATCC58025, targeted inactivation of the genes in the cluster suggested at least three genes respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Moreover, Bcstc5/Bcaba5 appeared to be approximately sixfold more highly expressed in ATCC58025 than in B05.10. As ABA is a compound of interest for biotechnology companies, several screening and mutagenesis programs were conducted to improve the ability B. cinerea to produce this compound at an industrial scale, i.e., up to 6 g l −1 (Gong et al ., ; Ding et al ., ; Shi et al ., ). The resulting ABA‐overproducing strains like ATCC58025 are impaired in conidiation and other developmental processes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, Bcstc5/Bcaba5 appeared to be approximately sixfold more highly expressed in ATCC58025 than in B05.10. As ABA is a compound of interest for biotechnology companies, several screening and mutagenesis programs were conducted to improve the ability B. cinerea to produce this compound at an industrial scale, i.e., up to 6 g l −1 (Gong et al ., ; Ding et al ., ; Shi et al ., ). The resulting ABA‐overproducing strains like ATCC58025 are impaired in conidiation and other developmental processes.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless the key enzyme, i.e., the sesquiterpene cyclase (STC) that is expected for the upstream cyclization step has not been identified so far. The described bcaba1–4 cluster does not include any STC‐coding gene suggesting that this gene is located elsewhere in the genome (Siewers et al ., ; Gong et al ., ). Complete genome sequencing of the two B. cinerea model strains B05.10 and T4 allowed the identification of five and six STC‐coding genes respectively (Amselem et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Alternatively, the Pseudomonas syringae effector HopAM1 enhances virulence via manipulation of sensitivity to ABA rather than initiating ABA biosynthesis ( Goel et al, 2008 ). Moving beyond bacterial delivery of effectors, some fungal pathogen encode ABA biosynthetic genes and have been shown to synthesize ABA including Cercopsora, Fusarium, Rhizoctonia (reviewed by Cao et al, 2011 ), and of particular relevance to this current study, B. cinerea ( Gong et al, 2014 ). Considering the mechanics of ABA promoted susceptibly, there is evidence that this causes reduced alterations in cell wall characteristics, ROS generation and callose deposition as well as defense gene expression ( Asselbergh et al, 2007 ; de Torres-Zabala et al, 2007 ; Cao et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…A similar link between ABA and suppression of ROS during attack by B. cinerea has been made in Arabidopsis ( L’Haridon et al, 2011 ). Given such observations it is unsurprising that B. cinerea strains can encode genes for ABA biosynthesis ( Gong et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies support the role of ABA in promoting virulence in plant‐ Botrytis interactions. ABA overproduction has been associated with enhanced virulence in some strains (Siewers et al , Gong et al , Ding et al ) and treatment with exogenous ABA was shown to promote virulence (Shaul et al ). The WRKY33 transcription factor is required for the downregulation of plant ABA biosynthesis and thus promotes immunity against Botrytis (Liu et al ).…”
Section: Introductionmentioning
confidence: 99%